The duality of silence and sound The effectiveness of opposites in modern Arabic poetry (Journal of the College of Basic Education, 2022)
The study includes research in the specificity of opposites in modern Arabic poetry, especially the duality of silence and sound, which constituted a poetic style and feature that carried with it a philosophical and poetic stance, embodying a paradox on the expressive and semantic level if their texts were taken from what is familiar to interrogate reality and insert it into a more suggestive poetic reality, as if the poets sought Through this duality, to form a prominent and influential image that has an aesthetic and interpretive dimension to form more profound and influential scenes. That is, it came to express their suffering and their psychological distress